IMPACT OF POLITICIAN’S LANGUAGE POLITENESS ON PUBLIC TRUST IN TALK SHOW - Kurniawan, Roni (Kantor Bahasa Maluku Utara, 2024)
This study examines the impact of politeness strategies used by politicians on public trust. The data is sourced from the YouTube channel